Aprender brincando: alfabetizando com o teatro de bonecos - SILVA, Ana Cristina Souza (2023)
The research deals with continuing education in Animation Theater entitled "Learning by playing: alphabetizing with puppet theater" for generalist teachers who work from the 1st to the 2nd year of Elementary School - Initial Years and Art in the city of Raposa- MA. To achieve this study objective, a training course in Animation Theater was offered to teachers working in the municipal teaching network of Raposa/MA in a face-to-face format, divided into five modules consisting of theoretical and practical activities and educational material. Twelve teachers, all specialists, participated in this study. As for the focus, we opted for the characteristics of the qualitative research approach, following the conjuncture of this investigation, the method of procedure selected was the cartographic research. The data collection instruments were: initial and final structured interviews, documentary research, professor's report, focus group, audiovisual record. To collect the data, online digital platforms were used through Google tools, such as Google Forms and Google Meet, in addition to the face-to-face form, with the first having the questionnaire expression of interest and registration; the second, audio and video for conducting interviews and focus groups. The analysis and interpretation of data with a qualitative approach was carried out using charts, tables and graphs to systematize the participants' speeches during the interviews (initial and final) into categories and subcategories. These data showed that most of the participating teachers had a lack of initial teacher training, in terms of contact with puppet theater. However, the data collected and analyzed in the post-intervention period demonstrate that the proposed continuing education course contributed to the participants acquiring and expanding their knowledge about the contributions of puppetry to the literacy process of Elementary School students Years Initials of the city of Barros e Kastrup (2019), Deleuze e Guattari (1995), Escóssia e Tedesco (2012), Goldenberg (1997), Minayo (2008), Thiollent (2009), Yin (2016), Santos (2003), Arantes (2017), Amaral (2004), Santana (2004), Vygotsky (1984). Nunes (2007), Alvarenga (2017), Oliveira (2008), Kishimoto (2002), Ferreiro eTeberosky (1985), Segel (1995), Blumenthal (2005), Yamane (2004), Sheehan (1969), Mármol (2019), Fusari; Ferraz (2001) Cunha (2005). Soares (2010), LDB (1996), C.F (1998), BRASIL (1998), PNE (2014), PCNS -Arte (1998), PCNEF (2000), BNCC (2017) it is DCTM (2019).